2015
DOI: 10.1007/s13311-015-0339-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances and the Future of Stem Cell Therapies in Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis is a progressive neurodegenerative disease of the motor neurons without a known cure. Based on the possibility of cellular neuroprotection and early preclinical results, stem cells have gained widespread enthusiasm as a potential treatment strategy. Preclinical models demonstrate a protective role of engrafted stem cells and provided the basis for human trials carried out using various types of stem cells, as well as a range of cell delivery methods. To date, no trial has demonstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 129 publications
(116 reference statements)
0
23
0
Order By: Relevance
“…The complex pathogenesis and limited efficacy of disease‐modifying therapies predicates an urgent need for novel treatment strategies. Recent studies examining cellular transplantation for neurological disorders2 prompted interest in cell‐based therapies for ALS, and several cell types and delivery strategies are being evaluated in preclinical and translational ALS studies 3, 4…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The complex pathogenesis and limited efficacy of disease‐modifying therapies predicates an urgent need for novel treatment strategies. Recent studies examining cellular transplantation for neurological disorders2 prompted interest in cell‐based therapies for ALS, and several cell types and delivery strategies are being evaluated in preclinical and translational ALS studies 3, 4…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies examining cellular transplantation for neurological disorders 2 prompted interest in cell-based therapies for ALS, and several cell types and delivery strategies are being evaluated in preclinical and translational ALS studies. 3,4 Human spinal cord-derived neural stem cell (HSSC) intraspinal transplantation as a therapeutic approach has progressed to clinical trials in ALS patients. This approach is supported by in vitro and in vivo preclinical studies [5][6][7][8][9] and demonstrated safety of HSSC intraspinal transplantation in Gottingen minipigs, 10,11 data which secured Food & Drug Administration approval to examine HSSC intraspinal transplantation in ALS patients.…”
Section: Introductionmentioning
confidence: 99%
“…The next criterion, concerning the delivery techniques for different stem cell types in ALS therapy, includes intra‐thecal, intra‐spinal, intra‐ventricular, intra‐muscular, and intra‐arterial routes of administration. Ultimately, the last condition refers to the integrity of stem cells, which must be clinically quantifiable (Goutman et al, 2015). This results in the need to track grafted cells from the moment of their transplantation until they reach the host environment.…”
Section: Clinical Advances In Stem Cell Therapies For Alsmentioning
confidence: 99%
“…This cellular imaging technique, combined with contrast agents, has been widely used in in vitro studies, where grafted cells with efficient labeling did not exhibit impaired survival, proliferation, self‐renewal or multipotency (Neri et al, 2008). Cell integrity also depends on the progression of the disease and changes in functional status in ALS patients, which are measured using the Revised ALS Functional Rating Scale (ALSFRS‐R) (Goutman et al, 2015). Additionally taken into account are also the estimated respiratory parameters and lifespan, as well as the records of a given number of assessed improvements in health as compared to control treatments.…”
Section: Clinical Advances In Stem Cell Therapies For Alsmentioning
confidence: 99%
“…Linga Reddy and Timothy Miller [13] that details the recent advances in RNA-based therapeutics for ALS and emphasizes the current progress in the preclinical and early clinical applications of antisense oligonucleotides and small interfering RNAs. The final paper, by our research group, then reviews the current progress in the development and application of stem cell-based therapies in ALS [14]. Briefly, we present preclinical data examining the therapeutic utility of various stem cell types and an overview of the paradigms that have progressed to early clinical trials; we include a brief update on the recent progress of our own clinical trial examining intraspinal transplantation of neural progenitor cells in patients with ALS.…”
mentioning
confidence: 99%